2007
DOI: 10.1152/ajpheart.01121.2006
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen-activated protein kinase mediates adenosine-induced alterations in myocardial glucose utilization via 5′-AMP-activated protein kinase

Abstract: Clanachan AS. p38 mitogen-activated protein kinase mediates adenosine-induced alterations in myocardial glucose utilization via 5Ј-AMP-activated protein kinase. Am J Physiol Heart Circ Physiol 292: H1978 -H1985, 2007. First published December 15, 2006; doi:10.1152/ajpheart.01121.2006.-Adenosineinduced acceleration of glycolysis in hearts stressed by transient ischemia is accompanied by suppression of glycogen synthesis and by increases in activity of adenosine 5Ј-monophosphate-activated protein kinase (AMPK). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
6
17
0
1
Order By: Relevance
“…These effects were inhibited by araA, compound C and AdipoR1 siRNA, indicating the involvement of AdipoR1-AMPK-dependent p38 activation in adiponectin-mediated IL-6 induction. It has also reported that AMPK is downstream molecule of p38 in the control of myocardial glucose metabolism (41). In this study, we found that p38 inhibitor SB203580 cannot antagonized the adiponectin or AICAR-increased AMPK phosphorylation and kinase activity.…”
Section: Discussionsupporting
confidence: 45%
“…These effects were inhibited by araA, compound C and AdipoR1 siRNA, indicating the involvement of AdipoR1-AMPK-dependent p38 activation in adiponectin-mediated IL-6 induction. It has also reported that AMPK is downstream molecule of p38 in the control of myocardial glucose metabolism (41). In this study, we found that p38 inhibitor SB203580 cannot antagonized the adiponectin or AICAR-increased AMPK phosphorylation and kinase activity.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, at the end of reperfusion, AMP-to-ATP ratios were similar between groups, an effect that agrees with the observed ratios at the end of reperfusion in AMPK-␣ 2 KO mice (7,53). Of interest is that glycogen levels in AMPK-␣ 2 DN hearts were elevated at the end of reperfusion in the presence of insulin, which correlates well with previous studies that demonstrated an inverse correlation between AMPK activity and glycogen content in both the heart (18,19) and skeletal muscle (3). This increase in glycogen content may be due to reduced phosphorylation of site 2 of glycogen synthase (20,50) or may be due to a greater shunting of glucose toward glycogen synthesis because of an inhibition of glycolysis (18).…”
Section: Discussionsupporting
confidence: 90%
“…Glycolysis and glucose oxidation rates were measured directly from the simultaneous production of 3 H2O (liberated at the enolase step of glycolysis) and 14 CO2 (liberated at the level of pyruvate dehydrogenase complex and in the citric acid cycle), respectively, from [5-3 H]glucose and [U- 14 C]glucose, as described previously (8 Calculation of the rate of proton production arising from exogenous glucose metabolism. When glucose (from endogenous or exogenous sources) is metabolized by glycolysis and subsequently oxidized 1:1, with the associated synthesis and hydrolysis of ATP, the net production of protons is zero.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we have demonstrated that inhibition of p38 mitogen-activated protein kinase (MAPK) inhibits the activation of AMPK, attenuates the rates of glycolysis and H ϩ production, as well as relieving the suppression of glycogen synthesis (14). Whether this mechanism persists in stressed hearts during reperfusion following severe ischemia and translates into cardioprotection has yet to be determined.…”
Section: Clanachan Asmentioning
confidence: 99%